Thyroid Leiomyosarcoma: A Rare Case Report - Juanita; Maulana, Aries; Yamin, Amalia; prihatni, Imeldi; Sungowati, Ni Ketut; Miskad, Upik Anderiani (Majalah Patologi Indonesia, 2025)
Background Primary thyroid leiomyosarcoma is a very rare tumor. The incidence is less than 0.01% of all primary thyroid tumors. Thyroid leiomyosarcoma are tumours showing smooth muscle differentiation, originating from thyroid gland vascular smooth muscle. Case Description Female, 47 years old, with lump on the left neck since 1 year ago, getting bigger in the last 3 months, no shortness of breath, no history of previous surgery. Physical examination revealed a mass was 13x6 cm in size, solid, firm.  Cytological features from fine needle aspiration biopsy (FNAB) showed cellular spindle cells with atypical, pleomorphic, hyperchromatic nuclei and  several normal thyroid follicles among them, sugesting  malignant thyroid tumor (Bethesda VI). Total thyroidectomy was performed, followed by histopathological examination. Microscopically showed proliferation of atypical, pleomorphic, hyperchromatic spindle cells with eosinophilic cytoplasm. The spindle cells arranged in fascicular and interlacing pattern. Several follicular thyroid are entrapped within this atypical spindle cells. Based on these finding, this case was diagnosed as anaplastic thyroid carcinoma. To confirm the diagnosis, immunohistochemical examination with cytokeratin, desmin and Ki-67 were performed and the result showed negative for cytokeratin, positive for desmin and Ki-67 was highly positive. Based on these results, a diagnosis of thyroid leiomyosarcoma was made. Discussion and Conclusion Differential diagnosis with other primary mesenchymal thyroid  tumors should be considered in the cases with atypical spindle cells microscopic appearance. The diagnosis of thyroid leiomyosarcoma based on cytology and histopathology is difficult to establish, therefore immunohistochemical staining is required to establish the accurate final diagnosis.